Is Marital Status a Risk Factor for Mental Disorders? A Case Study - Bora, Dibyajyoti; Das, Dhruba (Thailand Statistician, 2024)
In this article, we have studied whether marital status contributes to the occurrence and early onset of mental disorders. Moreover, the impact of mental disorder on present marital status and the simultaneous association of several socio-demographic factors on an affected marital status caused by the disorder were also studied. Data were collected from patients suffering from mental disorders aged 21 years through 60 years. Marital status and the occurrence of mental disorders are independent for both genders. An early-onset age of the disorder for both genders, especially for males is found, male patients have an early onset of 1.6 years compared to females. For both genders, the association between a strained marital life before the occurrence of the disorder and the age of onset of the disorder has been signiﬁcant. After marriage, male patients suffered from mental disorders earlier than their female counterparts. Consequently, the impact of the disorder on present marital status is very worrying with some negative outcomes. The disorder is significantly affecting all categories of marital status. An affected married life is closely associated with disease severity- those with declining illness status and those of younger ages more often reported an affected married life. Among the separated/divorced, 96.6% admit that they are separated/divorced because of the disorder. Male patients were 3.8 times more likely to undergo separation/divorce than females. Although disease severity is the most significant causal factor for affected marital status, simultaneously, some other socio-demographic factors are also found closely associated with the affected status.